Talent Mapping of the Howard Gartner Model for High School Students in Tangerang City Banten - Sara Sahrazad (Formosa Journal of Sustainable Research, 2022)
Talents and interests are things that are not easy to formulate for the development of high school students. Grade 12 students who are ending their studies need basic referrals for parents and students. The purpose of this study is to map the intelligence and talents possessed by students before graduating from high school (SMA), and to analyze the interests possessed by students. The respondents of this study were 12th grade high school students in the city of Tangerang. The number of respondents was 102 students. The research method used is descriptive statistical method. Based on the results of the study, students who have multiple intelligences of mathematical logic as many as 30 students achieve a percentage of 28.8%, while the smallest is interpersonal as many as 3 students by 2.5%. The implication of this research is that schools and teachers and parents of students can use these results as a reference for learning styles and specializations in a particular field, when they continue their studies and the field of work they will be involved in